Diatom type material in permanent slides does not need to be permanently unavailable for electron microscopy examination. Issue 2 (1st February 2021) - Majewska, Roksana; Taylor, Jonathan C.; Goosen, William E.
Abstract : The inability to thoroughly examine diatom type material existing only in resin‐mounted permanent slides is a common frustration for diatomologists. Here, we present an efficient, inexpensive, and straightforward technique to extract siliceous exoskeletons of diatoms from permanent slides prepared with commonly used mounting media. Van Heurck's slide constituting an isotype duplicate of  Proschkinia bulnheimii  var.  belgica, an entity with an uncertain taxonomic status, was deconstructed to allow thorough examination using scanning electron microscopy. Numerous specimens of the taxon, including intact frustules and specimens with complete areola occlusions, were recovered and documented. The extracted diatom material was sufficient to prepare two scanning electron microscopy specimens and reconstruct the permanent slide. The proposed approach may help overcome many of the taxonomic bottlenecks associated with the low resolution of information provided by older diatom descriptions and permanent slide observations.